EFFECT OF UN-IDEAL METHOD OF TOOTH BRUSHING ON GINGIVAE AMONG SECONDARY SCHOOL STUDENTS IN EPE LOCAL GOVERNMENT AREA OF LAGOS STATE NIGERIA - ADEOYE, KUKU M; KAZEEM, ADESANYA K.; YUSUF-BABATUNDE, A.M (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
This research seeks to estimate the effect of un-ideal method of tooth brushing on gingivae and sustainability among secondary school students of Epe Local Government Area of Lagos. The validated instrument was administered to forty (40) secondary school students in Ijebu Ode Local Government of Ogun State who were not part of the study. The test re-test reliability method was adopted at an interval of two weeks to determine the reliability of the instrument using Pearson product moment correlation confident (r). A sample of four (400) hundred secondary school students was selected with the aid of stratified sampling techniques to select the schools and simple random sampling method to select the respondents from each selected schools. Three hypotheses were formulated and tested using chi-square analysis of 0.05 level of significance. One hypothesis was accepted while the remaining two (2) hypotheses were rejected. The findings show that Tooth decay is a common global disease which can be reduced with good oral hygiene practice. The researcher recommends dental health education among others.